Influence of beam size and distribution of horizontal reinforcement on shear strength of RC deep beams - Rao, G. Appa; Prasad, B.S.R.K.; Rao, K. Ramamohan (Journal of Structural Engineering, 2024)
Twelve reinforced concrete deep beams of three different depths and two different percentages of horizontal shear reinforcement with two types of distribution were studied for understanding the size effect and influence of the distribution of horizontal shear reinforcement on the shear strength and the cracking behaviour. Three beam depths namely 300mm, 600mm and 1200mm provided with two different percentages of horizontal shear reinforcement of 0.2 and 0.3, which were distributed (i). uniformly throughout the depth and (ii). uniformly only over the middle third of the depth. The shear span-to-depth ratio was 0.75. The flexural tensile reinforcement was 1.5% and provided with 25mm clear cover. The test results showed that the mode of failure was signifi cantly altered by changing the beam depth. Sufficient ductility was achieved in small size beams, whereas relatively very high brittleness was observed in large size beams. As the quantity of horizontal shear reinforcement increases the shear strength and the deformability of the beams were found to be increased. The effect of the distribution of horizontal shear reinforcement along with the size effect seems to infl uence the strength and ductility of the beams. The uniform distribution of reinforcement over the middle third portion of the beam depth exhibited signifi cant improvement on the shear strength and ductility. A strong size effect has been observed on the shear strength of RC deep beams. There exists a non-negligible size effect on the diagonal strength of RC beams. When the beam depth is increased from 600mm to 1200mm, there has been a decrease of diagonal strength ranging from 20% to 25%, while it ranges between 35% to 55% when the depth is increased from 300mm to 1200mm.